Exploring Roman ritual behaviours through plant remains from Pannonia Inferior - Reed, K; Lodwick, L; Leleković, T; Vulić, H (Routledge, 2018)
The recovery of new plant remains from eastern Croatia are discussed here in order to determine their ritual significance and how this evidence may fit into chronological and regional observations on ritual plant offerings in the Roman world. Samples collected from inhumations, cremations and an altar dedicated to Silvanus Domesticus, dating from the 2nd to 4th centuries AD, are presented and show that a range of more ‘common’ plant remains, such as cereals and pulses, were an important part of ritual life. These results are also compared to the growing archaeobotanical data collected from shrine and cremation burials across Europe. Although the archaeobotanical data from the Croatian sites are limited, the increasing evidence of ritual plant use allows observations regarding the wider context of Roman social and religious change.